O kreatywności generatywnej sztucznej inteligencji - Łukawski, Adam (Warsaw Instytut Badań Edukacyjnych (Educational Research Institute), 2023)
Can artificial intelligence be creative? The topic of artificial intelligence’s creativity is recently a subject of intense debates and analyses. However, it is important to distinguish between creativity resulting from true innovation and creativity that is the result of processing and reconfiguring existing data. This raises the question: is AI truly creative, or does it merely imitate human creativity using advanced algorithms?
FRIS
Editorial review
Keywords: MetamusicX:Transdisciplinary Encounters in and Beyond Music